Students’ Perceptions of the Benefits of Using Character.AI for Speaking Practice - Roni Kurniawan; Maida Norahmi; Akhmad Fauzan; Alvionita Damayanti (Journal of English Language and Education, 2026)
This study explores students’ perceptions of the role of Character.AI in developing speaking skills and supporting adaptive communicative practice. Most existing studies on AI in language learning primarily focus on tools that rely on structured or predefined prompts, which tend to be monotonous and less effective in fostering adaptive speaking development. However, limited attention has been given to more interactive, persona-driven AI platforms that can simulate real-life communication. To address this gap, this study employed a qualitative phenomenological approach involving five (5) eighth-semester students of the English Education Study Program who had experience using Character.AI for speaking practice. Data were collected through triangulation methods, including questionnaires and semi-structured interviews, and analysed using thematic analysis. The findings revealed that Character.AI contributes to the development of speaking skills, including improvements in fluency, confidence, motivation, vocabulary, willingness to speak, as well as a reduction in speaking anxiety. It also facilitates adaptive communicative practice by promoting adaptability, flexibility and accessibility in speaking activities. However, some limitations were identified, particularly in generating occasionally unnatural responses, indicating that it cannot fully replace authentic human interaction. Therefore, Character.AI is best utilized as a supplementary tool to support students in preparing for real-life communication.